Hydrogen-rich Syngas Production from Ethanol Dry Reforming on La-doped Ni/Al2O3 Catalysts: Effect of Promoter Loading - Mahadi, Bahari; Goo, Boon Chin; Pham, Thong L. M.; Tan, Ji Siang; Danh, Huong T.; Nurul, Ainirazali; Vo, Dai-Viet N. (Elsevier Ltd, 2016)
Ethanol dry reforming has been studied over La-promoted Ni catalysts supported on Al2O3 with different promoter loadings at varying CO2 partial pressure of 20-50 kPa. Catalysts were prepared via co-impregnation technique and characterized using BET surface area, X-ray diffraction measurement, temperature-programmed calcination and scanning electron microscopy. Doped and undoped catalysts possessed high surface area of about 86-108 m2 g-1 and La promoter was well-dispersed on support surface. Xray diffraction measurements indicated the formation of La2O3, NiO and NiAl2O4 phases in line with temperature-programmed calcination results. La-addition enhanced the dispersion of NiO particles and reduced the agglomeration of metal oxides. Both C2H5OH and CO2 conversions improved with increasing CO2 partial pressure rationally due to the growing secondary CO2 reforming of CH4 reaction. The ratio of H2/CO produced from ethanol dry reforming varied from 1.1 to 1.4 favored for usage as feedstocks of Fischer-Tropsch synthesis. The yield of H2 and CO also enhanced with increasing CO2 partial pressure whilst the optimal La loading in terms of C2H5OH conversion was observed at 3%La and catalytic activity increased with promoter addition reasonably owing to the redox properties of La promoter. CO2 reforming of ethanol reaction appeared via ethanol decomposition to CH4 intermediate product, which was subsequently converted to CO and H2 mixture through CH4 dry reforming reaction.